The Method of Increasing the Cognitive Potential of a Person (R. Feuerstein and R. Guzman) - Mayzel, O.V. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2016)
The article is devoted to the description and analysis of method of development of intelligence Reuven of Feierstein, a distinguished Israeli scholar and a follower of J. Piaget and L.S. Vygotsky. Based on theoretical experience of his great predecessors R. Feuerstein has developed practical methods to develop cognitive functions in children. A significant role is given to training in adult (mediator), whose tasks include the direction and organization of the learning process by using specially developed techniques. Later, Israeli psychologist R. Guzman has adapted these methods for children suffering from Attention Deficient Hyperactivity Disorder, as well as for born blind people. The exception of the visual perception channel in the proposed set of original methods allows children suffering from Attention Deficient Hyperactivity Disorder, to avoid extra stimulation of brain activity and to focus on completing the tasks given by the mediator. Meanwhile, using the tactile methods when working with born blind people, on the contrary, promotes creating “the library of visual images”. Carrying out consistent lessons based on tactile methodology lead to the behavior correction of the children who suffer from Attention Deficient Hyperactivity Disorder and of born blind people of all age groups, as well as it caused the development of immature or absent cognitive functions. Статья посвящена описанию и анализу метода развития интеллекта Рувена Фейерштейна – выдающегося израильского ученого, современника и последователя Жана Пиаже и Льва Семеновича Выготского. Опираясь на теоретический опыт своих великих предшественников, Р. Фейерштейн разработал практические методы, позволяющие развивать когнитивные функции у ребенка. Значимая роль в обучении отводится взрослому (посреднику, или медиатору), в задачи которого входят направление и организация процесса обучения при помощи специально разработанных методик. Позже израильский психолог Р. Гузман адаптировал эти методики для детей, страдающих синдромом дефицита внимания и гиперактивности, а также для незрячих от рождения людей. Исключение зрительного канала восприятия в предложенном наборе оригинальных методик позволяет детям, страдающим синдромом дефицита внимания и гиперактивности, избежать гиперстимуляции деятельности мозга и сосредоточиться на выполнении предлагаемых медиатором задач. При этом использование тактильных методик в работе с пациентами, невидящими от рождения, напротив, способствует формированию у них «библиотеки зрительных образов». Результатом проведения последовательных занятий с использованием тактильных методик является коррекция поведения детей любого возраста, страдающих синдромом дефицита внимания и гиперактивности, или невидящих от рождения, а также развитие и формирование у них когнитивных функций.